Design, Development, and Testing of a Compact Underwater ROV for Inspection and Exploration - Mohd Shahrieel Mohd Aras; Teoh Yi Xin; Fauzal Naim Zohedi; Mohd Bazli Bahar; Mohamad Haniff Harun; Alias Khamis; Zairi Ismael Rizman (Journal of Studies in Science and Engineering)
Underwater exploration has long been a high-risk endeavor requiring trained divers and specialized equipment, creating a growing demand for low-cost, safe, and efficient alternatives. This study presents the design and development of a four-degree-of-freedom (4-DOF) underwater Remotely Operated Vehicle (ROV) aimed at performing basic submerged inspection tasks. The ROV is designed using Fusion 360 software, with finite element analysis (FEA) ensuring structural integrity under underwater pressure. Key performance metrics, including buoyancy, acceleration, velocity, and stability, are evaluated to validate the system's operation. The final deliverable is a durable, lightweight acrylic ROV frame with negative 90% buoyancy, equipped with sensors, cameras, and weatherproof housing for full underwater functionality. An Arduino Uno microcontroller manages the control system, enabling real-time integration of sensors and camera feeds. This project offers a scalable, low-cost solution for small-scale underwater applications, providing a foundation for future enhancements in maneuverability and data acquisition.